Integrated cashew shelling - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Cashew nuts were originally a Brazilian crop but are now grown in Central and South America, in East and West Africa and in Asia. Shelling cashew nuts is generally a time and energy consuming process. A London-based company has now developed...